2021
DOI: 10.2298/tsci191212026l
|View full text |Cite
|
Sign up to set email alerts
|

Fractal diffusion-reaction model for a porous electrode

Abstract: Fractal modifications of Fick?s laws are discussed by taking into account the electrode?s porous structure, and a fractal derivative model for diffusion-reaction process in a thin film of an amperometric enzymatic reaction is established. Particular attention is paid to giving an intuitive grasp for its fractal variational principle and its solution procedure. Extremely fast or extremely slow diffusion process can be achieved by suitable control of the electrode?s surface morphology, a sponge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Another example is the motion of the Moon, which is naturally periodic; however, if we measure its motion at an extremely far distance, its motion becomes stochastic, and the Heisenberg-like uncertainty principle works for the Moon [9]. He and Qian showed that the fractal diffusion process in water depends on the fractal dimensions [10], and other scientists also discussed the fractional advection-reaction-diffusion process [11] and the fractal diffusion-reaction process [12]. A cocoon's air/moisture permeability and its thermal property can best be revealed by the fractal-fractional model [13,14], and the fractal microelectromechanical systems show even more amazing properties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the motion of the Moon, which is naturally periodic; however, if we measure its motion at an extremely far distance, its motion becomes stochastic, and the Heisenberg-like uncertainty principle works for the Moon [9]. He and Qian showed that the fractal diffusion process in water depends on the fractal dimensions [10], and other scientists also discussed the fractional advection-reaction-diffusion process [11] and the fractal diffusion-reaction process [12]. A cocoon's air/moisture permeability and its thermal property can best be revealed by the fractal-fractional model [13,14], and the fractal microelectromechanical systems show even more amazing properties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%